2012
DOI: 10.1016/j.ntt.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Selective effects of perinatal ethanol exposure in medial prefrontal cortex and nucleus accumbens

Abstract: Ethanol exposure during development is the leading known cause of mental retardation and can result in characteristic physiological and cognitive deficits, often termed Fetal Alcohol Spectrum Disorders (FASD). Previous behavioral findings using rat models of FASD have suggested that there are changes in the nucleus accumbens (NAC) and medial prefrontal cortex (mPFC) following ethanol exposure during development. This study used a rat model of FASD to evaluate dendritic morphology in both the NAC and mPFC and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 81 publications
3
43
0
Order By: Relevance
“…Such damage may contribute to the impaired impulse control and social deficits observed in children with FASD throughout life. In particular, rodent models of developmental alcohol exposure result in increased caspase-3 expression in the central nucleus of the amygdala (Mitchell & Snyder-Keller, 2003), long-term reductions to amygdalar opioid signaling (Lugo, Wilson, & Kelly, 2006), and altered synaptic connectivity and neuronal loss in the amygdala (Balaszczuk, Bender, Pereno, & Beltramino, 2011; Cullen et al, 2013; Zhou et al, 2010) and the prefrontal cortex (Hamilton, Whitcher, & Klintsova, 2010; Ikonomidou et al, 2000; Lawrence, Otero, & Kelly, 2012; Whitcher & Klintsova, 2008). Dysfunction of these brain areas could contribute to disruptions in social and play behavior observed in AE rats.…”
Section: Discussionmentioning
confidence: 99%
“…Such damage may contribute to the impaired impulse control and social deficits observed in children with FASD throughout life. In particular, rodent models of developmental alcohol exposure result in increased caspase-3 expression in the central nucleus of the amygdala (Mitchell & Snyder-Keller, 2003), long-term reductions to amygdalar opioid signaling (Lugo, Wilson, & Kelly, 2006), and altered synaptic connectivity and neuronal loss in the amygdala (Balaszczuk, Bender, Pereno, & Beltramino, 2011; Cullen et al, 2013; Zhou et al, 2010) and the prefrontal cortex (Hamilton, Whitcher, & Klintsova, 2010; Ikonomidou et al, 2000; Lawrence, Otero, & Kelly, 2012; Whitcher & Klintsova, 2008). Dysfunction of these brain areas could contribute to disruptions in social and play behavior observed in AE rats.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies showed decreased spine density in OFC and either no change (66) or a decrease (67) in mPFC in adult brains.…”
Section: Factors Influencing Prefrontal Developmentmentioning
confidence: 99%
“…In some models, histological studies showed that these volume reductions corresponded to reduced neuron numbers (Berman & Hannigan, 2000; Ieraci & Herrera, 2007; Miller, 2006; Olney, 2004). More detailed examinations found evidence of altered dendritic length and spine density (Berman & Hannigan, 2000; Cui et al, 2010; Lawrence, Otero, & Kelly, 2012; Susick, Lowing, Provenzano, Hildebrandt, & Conti, 2014), and found evidence of disrupted organization of cortical sensory areas (Margret et al, 2006; Medina, Krahe, & Ramoa, 2005; Miller & Potempa, 1990). Additionally, in several cortical and subcortical brain regions there are findings of reduced GABAergic cell density, suggesting that inhibitory circuits in the cerebral cortex may be especially vulnerable to ethanol toxicity (Coleman et al, 2012; Sadrian, Lopez-Guzman, Wilson, & Saito, 2014; Sadrian et al, 2013).…”
Section: Introductionmentioning
confidence: 99%